Microgrids with energy storage systems as a means to increase power resilience: An application to office buildings. (1st April 2019) - Rosales-Asensio, Enrique; de Simón-Martín, Miguel; Borge-Diez, David; Blanes-Peiró, Jorge Juan; Colmenar-Santos, Antonio
Abstract: This work describes a methodology to quantify the benefits from both a business-related and energy resilience perspectives provided by a microgrid based on photovoltaic solar energy and electrochemical energy storage integrated in large buildings, such as office buildings not open to the general public, which is presented as case study. First it has been identified how, by using distributed renewable energy sources (in particular, photovoltaic solar energy) and electrochemical energy storage systems, the life-cycle cost of the energy in a microgrid connected to the electrical network can be reduced significantly. As novel approach, it has been evaluated how this microgrid design can increase the resilience of a power customer supply, quantified as the time period the microgrid is able to feed an electrical consumer at an outage, which it results of great importance for large office buildings that are used to have several critical loads, such as data servers and data processing centers. It was found that, by adding photovoltaic solar energy and electrochemical storage, it is possible to extend the power resilience of this sort of power customers achieving an average survival time to a power cut of 4 h thanks to the proposed solar photovoltaic and energy storage system. Then, the microgrid could save $ 112, 410 in energy over the 20-year life cycle of the facility, while increasing the amount of time it can survive a power outage. The proposed methodology presented in this paper provides a model that can be applied to other case studies and scenarios where an alternative to the classic diesel-based emergency supply systems are needed. Graphical abstract: Image 1 Highlights: A methodology to quantify the resilience PV/storage benefits is presented. A case study at an office building not open to the general public is conducted. Microgrid LCOE was reduced for a grid connected operation mode. By including PV/storage to the microgrid, outage survivability is extended. Microgrid could save $ 112, 410 in energy over the 20-year life cycle of the facility.